Psoriasis and other complex trait dermatoses: from loci to functional pathways - Capon, Francesca (2011)
Driven by advances in molecular genetic technologies and statistical analysis methodologies, there have been huge strides taken in dissecting the complex genetic basis of many inflammatory dermatoses. One example is psoriasis where application of classical linkage analysis and genome wide association investigation has identified genetic loci of major and minor effect. Although most loci independently have modest genetic effect, they identify important biological pathways potentially relevant to disease pathogenesis and therapeutic intervention. In the case of psoriasis these appear to involve the epidermal barrier, NF-κB mechanisms and Th17 adaptive immune responses. The advent of next generation sequencing methods will permit a more detailed and complete map of disease genetic architecture, a key step in developing personalised medicine strategies in the clinical management of the complex inflammatory dermatoses.